Regional targeting of purpose driven wetlands: success or failure? - Geranmayeh, Pia; Speks, Amanda; Blicharska, Malgorzata; Futter, Martyn; Collentine, Dennis (Frontiers in Sustainable Resource Management, 2023)
In the past 30 years, Swedish EU Rural Development Programme (RDP) financing for constructed wetlands (CWs) had two goals: nutrient reduction and biodiversity conservation. Since 2007, at least 1718 CWs have been implemented. However, their cost effectiveness has been difficult to assess as defined targets for improvements were lacking. In 2013, Sweden set up regional (county) targets for new CWs to mitigate eutrophication and conserve biodiversity as part of a six-year plan under the RDP. Here, we investigate if the increase in targeting was effective, in particular if the 15 participating counties achieved their stated goals. We also compare CW characteristics during the regionally targeted period (2014-2020) with the preceding untargeted period (2007-2013). The results indicate that regional targets were not achieved. Most counties set lower targets for biodiversity conservation than for nutrient reduction. Hence, by 2020 more counties exceeded targets for the former than for the latter. Budget share allocated to the two goals was not decisive, instead the outcome could be attributed to prioritization, budget controls, timing consistency, decision criteria consistency and goal setting. During both periods half of the CWs were funded for each purpose, yet the number of wetlands constructed decreased by 82% in the second period. Landowners may have prioritized biodiversity CWs as construction costs were higher for nutrient retention CWs and costs were mostly not fully covered by the RDP. Furthermore, targets were not budget limited, which meant that county-level allocation of funds could be shifted to finance CWs that did not meet the intended purpose. To increase overall measure effectiveness, we suggest that the distribution of national funds for CWs should be divided between the two purposes identified at the regional level and that reallocation of funds only be permitted in accordance with redefinition at the county level.